Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1089/apc.2015.0040
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Response to Antiretroviral Therapy by Sex and Hepatitis C Infection Status

Abstract: Hepatitis C virus (HCV) co-infection and biological sex may each affect response to antiretroviral therapy (ART), yet no studies have examined HIV-associated outcomes by both HCV status and sex. We conducted a cohort study of HIV-infected adults initiating ART in Kaiser Permanente California during 1996-2011. We used piecewise linear regression to assess CD4 changes by sex and HCV status over 5 years. We used Cox regression to estimate hazard ratios (HR) by sex and HCV status for HIV RNA <500 copies/mL over 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
16
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 43 publications
5
16
0
1
Order By: Relevance
“…Hepatitis C virus (HCV) status was determined by HCV-antibody tests or HCV RNA levels, or, for KPNC, by inclusion in the KPNC viral hepatitis registry, as previously described. 22 …”
Section: Methodsmentioning
confidence: 99%
“…Hepatitis C virus (HCV) status was determined by HCV-antibody tests or HCV RNA levels, or, for KPNC, by inclusion in the KPNC viral hepatitis registry, as previously described. 22 …”
Section: Methodsmentioning
confidence: 99%
“…Numerous studies have found that hepatitis B virus (HBV), hepatitis C virus (HCV), and CMV coinfections were associated with poor CD4 + T‐cell immune recovery in HIV‐1‐infected individuals on ART. The precise mechanism by which HBV, HCV, and CMV coinfections may have deleterious effects on CD4 + T‐cell count recovery is unclear.…”
Section: Potential Mechanisms Of Incomplete Immune Reconstitutionmentioning
confidence: 99%
“…In a recent paper by Marcus et al, 39 it was shown that HIV/HCV coinfected adults have delayed CD4 + T cell reconstitution on ART, relative to their monoinfected counterparts. Similarly, a meta-analysis conducted by Tsiara et al 40 in 2013 of 21 studies involving 22,533 adult patients reported that even though HCV had a demonstrable adverse effect on immune reconstitution in the first 2 years of ART, this trend was not sustained in the long term.…”
Section: Discussionmentioning
confidence: 99%